Transient Viral Activation in Human T Cell Leukemia Virus Type 1-Infected Macaques Treated With Pomalidomide - Gutowska, Anna; McKinnon, Katherine; Sarkis, Sarkis; Doster, Melvin N.; Bissa, Massimiliano; Moles, Ramona; Stamos, James D.; Rahman, Mohammad Arif; Washington-Parks, Robyn; Davis, David; Yarchoan, Robert; Franchini, Genoveffa; et al. (Frontiers in Medicine, 2022)
(CTL) and natural killer (NK) cells, suggesting the virus has developed effective mechanisms to counteract host immune surveillance. We recently showed that in vitro treatment of HTLV-1-infected cells with the drug pomalidomide (Pom) increases surface expression of MHC-I, ICAM-1, and B7-2, and significantly increases the susceptibility of HTLV-1-infected cells to NK and CTL killing, which is dependent on viral orf-I expression. We reasoned that by restoring cell surface expression of these molecules, Pom treatment has the potential to reduce virus burden by rendering infected cells susceptible to NK and CTL killing. We used the rhesus macaque model to determine if Pom treatment of infected individuals activates the host immune system and allows recognition and clearance of HTLV-1-infected cells. We administered Pom (0.2 mg/kg) orally to four HTLV-1-infected macaques over a 24 day period and collected blood, urine, and bone marrow samples throughout the study. Pom treatment caused immune activation in all four animals and a marked increase in proliferating CD4+, CD8+, and NK cells as measured by Ki-67+ cells. Activation markers HLA-DR, CD11b, and CD69 also increased during treatment. While we detected an increased frequency of cells with a memory CD8+ phenotype, we also found an increased frequency of cells with a Treg-like phenotype. Concomitant with immune activation, the frequency of detection of viral DNA and the HTLV-1-specific humoral response increased as well. In 3 of 4 animals, Pom treatment resulted in increased antibodies to HTLV-1 antigens as measured by western blot and p24Gag ELISA. Consistent with Pom inducing immune and HTLV-1 activation, we measured elevated leukotrienes LTB4 and LTE4 in the urine of all animals. Despite an increase in plasma LTB4, no significant changes in plasma cytokine/chemokine levels were detected. In all cases, however, cellular populations, LTB4, and LTE4 decreased to baseline or lower levels two weeks after cessation of treatment. These results indicated that Pom treatment induces a transient HTLV-1-specific immune activation in infected individuals, but also suggest Pom may not be effective as a single-agent therapeutic.